Establishing processes in producing dicalcium phosphate, octacalcium phosphate and gelatin from monkfish (Lophius vomerinus) bones - Swart, Jasmin (Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.